21.0k views
24 votes
Solve for X
2.4x +3 = 6.6

2 Answers

6 votes

Answer:

x=1.5

Explanation:

2.4X=6.6-3

subtract 3 from both sides of the equestion

subtract 3 from 6.6

divide each trem by 2.4 and simplify

divide each term 2.4x =3.6 by 2.4

2.4=3.6

2.4 2.4

cancel the common factor of 2.4

X=3.6

2.4

divide 3.6 by 2.4

X=1.5

User Dare
by
5.3k points
10 votes

2
.
4

+
3
=
6
.
6 is your answer
User Ashen Madusanka
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.